Preparation and Evaluation of Antihypercholesterolemic Activity of Atorvastatin Calcium-Maleic Acid Co-Amorphous Solids - Yudi Wicaksono; Shofiatul Izzah Al Amaliyah; Finas Rahmayanti; Viddy Agustian Rosidi; Lina Winarti; Dwi Setyawan (Science and Technology Indonesia, 2022)
Atorvastatin calcium is a statin drug used for antihypercholesterolemic. The oral bioavailability of atorvastatin calcium is relatively low because it is poorly soluble in water. The low oral bioavailability of the drug causes a decrease in its therapeutic effectiveness. This study aimed to increase the solubility of atorvastatin calcium through the formation of co-amorphous solids and evaluate its activity as antihypercholesterolemic. Atorvastatin calcium was prepared into co-amorphous solids with a maleic acid coformer using the spray drying method. Solids characterization was carried out using Powder X-Ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transforms Infra Red (FTIR), and Scanning Electronic Microscopy (SEM). The solubility test was carried out using the shaking method, while the evaluation of antihypercholesterolemic was carried out in vivo in experimental animals. The results of the analysis of diffractograms, thermograms, FTIR spectra, and micrograph images showed that the atorvastatin calcium-maleic acid solids prepared by spray drying were a co-amorphous solid. The atorvastatin calcium-maleic acid co-amorphous solids had a greater solubility in water (p<0.05) when compared to pure atorvastatin calcium. However, the in vivo antihypercholesterolemic activity results in experimental animals showed that the cholesterol-lowering activity of the atorvastatin calcium-maleic acid co-amorphous solidswas not significantly different (p>0.05) with pure atorvastatin calcium. This phenomenon is thought to be because atorvastatin calcium from co-amorphous solids in solution is more present as a charged fraction, affecting the permeability and absorption process.